2016
DOI: 10.1063/1.4942472
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical cross sections for positron scattering from the pentane isomers

Abstract: Isomerism is ubiquitous in chemistry, physics, and biology. In atomic and molecular physics, in particular, isomer effects are well known in electron-impact phenomena; however, very little is known for positron collisions. Here we report on a set of experimental and theoretical cross sections for low-energy positron scattering from the three structural isomers of pentane: normal-pentane, isopentane, and neopentane. Total cross sections for positron scattering from normal-pentane and isopentane were measured at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Positron scattering cross sections or calculated interaction parameters also find practical application in energy deposition models [7]. There have been many recent studies on positron scattering from biological molecules [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Positron scattering cross sections or calculated interaction parameters also find practical application in energy deposition models [7]. There have been many recent studies on positron scattering from biological molecules [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…They found the three isomers behaved similarly, however since their work is not differential in angle, we expect that it is possible to see differences between these isomers for differential electron scattering from these isomers. A quite complete survey on electron and positron collisions with isomers of hydrocarbons and isomers of other molecules can be found in [11].…”
Section: Introductionmentioning
confidence: 99%
“…We further demonstrated that the bonding effect, chain length (closed or open), and atom layout within a molecular target all have an effect on scattering. To explore these effects thoroughly, we studied the isomers 23 of isoprene and 1,2-butadiene.…”
Section: ■ Introductionmentioning
confidence: 99%